Translational glycobiology: from bench to bedside. (October 2019) - Axford, John; Alavi, Azita; Cummings, Rick; Lauc, Gordan; Opdenakker, Ghislain; Reis, Celso; Rudd, Pauline
The importance of sugars to protein function is real and is of significant clinical relevance. Technology advances enable large population studies to be carried out, shedding light on individual sugar variation and variations with time. Three-dimensional mass spectroscopy on solid pathological specimens is going to open up a whole new world of pathology visualisation. The door is now open to exploit carbohydrate recognition in new therapeutics by identifying novel biomarkers in cancer to aid diagnosis, and also providing therapeutic targets for treatment. Glycan age correlates with biological age. This means we can map the reversal of biological age with exercise and diet.